Safety, pharmacokinetic, and pharmacodynamic study of sibofimloc, a novel FimH blocker in patients with active Crohn's disease. Issue 5 (18th March 2022) - Reinisch, Walter; Hébuterne, Xavier; Buisson, Anthony; Schreiber, Stefan; Desreumaux, Pierre; Primas, Christian; Paillarse, Jean‐Michel; Chevalier, Grégoire; Bonny, Christophe
Abstract: Background and Aim: Expression of FimH adhesin by invasive Escherichia coli in the gastrointestinal tract of patients with Crohn's disease (CD) facilitates binding to epithelial glycoproteins and release of pro‐inflammatory cytokines. Sibofimloc is a first‐in‐class FimH blocker that showed little systemic absorption in healthy volunteers. The current study evaluated systemic absorption, safety, and effect on inflammatory biomarkers of sibofimloc in patients with CD. Methods: This was an open‐label, multicenter phase 1b study in adults with active CD. In part 1, two patients received a single oral dose of 3000‐mg sibofimloc followed by 1500 mg b.i.d. for 13 days. In part 2, six patients received 1500‐mg sibofimloc b.i.d. for 13 days. Blood was drawn for pharmacokinetic and biomarker analysis, and stool was collected for biomarker and microbiome analysis. Results: Eight patients with active ileal or ileocolonic CD were enrolled into the study. Systemic sibofimloc exposure was low. Sibofimloc was well tolerated with only grade 1–2 events observed. Several pro‐inflammatory biomarkers, including IL‐1β, IL‐6, IL‐8, TNF‐α, IFN‐γ, and calprotectin, were decreased in stool by end of study. Conclusions: This first study of the novel FimH blocker, sibofimloc, in patients with active CD demonstrated minimal systemic exposure with good tolerance, while decreasing several inflammatory biomarkers. EudraCT number: 2017‐003279‐70.